Great public speaking an audience in the palm of your hand - Leigh, Richard; Video Education Australasia (Australia : Video Education Australasia, 2004)
The program delves into three complete case studies in corporate, social, and school settings and investigates content, delivery and the speech all covered in an enlightening and engaging way
Title from title screen
Executive producer, Mark McAuliffe ; editor, Paul Sutherland ; grapjics, Jeremy Lines ; sound, Wayne Martin ; camera, Richard Leigh
Voice over: Amy Blackmur
Keywords: Public speaking; Public speaking -- Psychological aspects